Redes sociales como medio de comunicación publicitaria por emprendedores en la ciudad de Babahoyo periodo marzo – mayo 2020 - Umanante Torres, Joel Steven (2020)
In the present case of study analyzed the impact of social networks as advertising communication media by entrepreneurs from the Babahoyo canton. It was carried out in order to determine the importance of these social platforms in people's lives. For the successful search for information, this work cost a mixed qualitative and quantitative research. Interviews were conducted with 2 entrepreneurs to know in depth what was the handling they gave to social networks when they advertised their products or services. To understand the advertising area, an additional interview was conducted with a person specialized in the subject. Citizen surveys were also conducted to find out their opinion on the consumption of advertising on social networks. With the project concluded, it was possible to deduce that social networks, in addition to being communication media, are feasible channels for the advertising of ventures. In addition, recommendations could be obtained regarding a better use for the benefit of future and current entrepreneurs when making their advertisements.